PRESCRIPTION AUDIT IN OUTPATIENT DEPARTMENTS OF TERTIARY CARE HOSPITALS; FACTS AND RECOMMENDATIONS - Muhammad Wasiullah Khan (Army Medical College Rawalpindi, 2021)
Objective: To evaluate written prescriptions according to a checklist based on WHO guidelines (prescription audit). To compare prescriptions of senior and junior physicians and to provide data and recommendations.